2016
DOI: 10.1007/s11249-016-0776-6
|View full text |Cite
|
Sign up to set email alerts
|

The Tribofilm Formation of ZDDP Under Reciprocating Pure Sliding Conditions

Abstract: The anti-wear and anti-seizure performance and action mechanisms of zinc dithiophosphate (ZDDP) have been investigated under reciprocating pure sliding conditions to simulate piston ring and cylinder liner assembly, using new techniques. The Mini Traction Machine-Space Layer Imaging is a useful method for monitoring tribofilm formation by ZDDPs. However, tests are generally carried out in mixed sliding-rolling conditions and ZDDP film formation in reciprocating pure sliding conditions is rarely investigated. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 22 publications
3
23
0
1
Order By: Relevance
“…However it can be seen that ZDDP film formation rate is much slower with 0.1 wt% N dispersant concentration. These results also confirm the rapid formation of sulphide in the film in pure sliding, reciprocating contact, as noted by Shimizu et al [28].…”
Section: Influence Of Dispersant On Zddp Reaction Ratesupporting
confidence: 91%
See 1 more Smart Citation
“…However it can be seen that ZDDP film formation rate is much slower with 0.1 wt% N dispersant concentration. These results also confirm the rapid formation of sulphide in the film in pure sliding, reciprocating contact, as noted by Shimizu et al [28].…”
Section: Influence Of Dispersant On Zddp Reaction Ratesupporting
confidence: 91%
“…The MTM was also used in reciprocating, pure sliding mode to study the influence of dispersants on initial ZDDP film formation [28]. A stationary MTM ball is loaded at 20 N against an MTM disc that rotates back and forth at 20 Hz over a stroke length of 4 mm.…”
Section: Reciprocating Mtm To Study Initial Zddp Film Formationmentioning
confidence: 99%
“…The mini traction machine-space layer imaging (MTM-SLIM), PCS Instrument is a well-known and useful method to monitor ZDDP tribofilm growth in situ, and its use to study the kinetics of ZDDP tribofilm growth has been reported widely [11][12][13][14][15][16][17][18][19][20][21][22]. In this paper, MTM-SLIM has been used to monitor ZDDP tribofilm formation and wear on the ferrous counter-surface rubbed against Al-Si alloys.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Shimizu and Spikes found that initial tribofilm formation on Fe alloys is S rich, and subsequently becomes more Zn and P rich. [31] However, it is reasonable to expect that S will have stronger bonding interactions with Fe than the Si-O terminated substrate utilized here. This could explain why our films initially grow more Zn and P rich.…”
Section: Resultsmentioning
confidence: 90%